A Magneto-Optical Nanoplatform for Multimodality Imaging of Tumors in Mice - Song, Guosheng; Zheng, Xianchuang; Wang, Youjuan; Xia, Xin; Chu, Steven; Rao, Jianghong (ACS nano, 2019)
Multimodality imaging involves the use of more imaging modes to image the same living subjects and is now generally preferred in clinics for cancer imaging. Here we present multimodalityMagnetic Particle Imaging (MPI), Magnetic Resonance Imaging (MRI), Photoacoustic, Fluorescentnanoparticles (termed MMPF NPs) for imaging tumor xenografts in living mice. MMPF NPs provide long-term (more than 2 months), dynamic, and accurate quantification, in vivo, of NPs and in real time by MPI. Moreover, MMPF NPs offer ultrasensitive MPI imaging of tumors (the tumor ROI increased by 30.6 times over that of preinjection). Moreover, the nanoparticle possessed a long-term blood circulation time (half-life at 49 h) and high tumor uptake (18% ID/g). MMPF NPs have been demonstrated for imaging breast and brain tumor xenografts in both subcutaneous and orthotopic models in mice via simultaneous MPI, MRI, fluorescence, and photoacoustic imaging with excellent tumor contrast to normal tissues.